Leveraging single-cell and multi-omics approaches to identify MTOR-centered deubiquitination signatures in esophageal cancer therapy - Tian, Kang; Yao, Ziang; Pan, Da (Frontiers in Immunology, 2024)
BackgroundEsophageal squamous cell carcinoma (ESCC) remains a significant challenge in oncology due to its aggressive nature and heterogeneity. As one of the deadliest malignancies, ESCC research lags behind other cancer types. The balance between ubiquitination and deubiquitination processes plays a crucial role in cellular functions, with its disruption linked to various diseases, including cancer.MethodsOur study utilized diverse analytical approaches, encompassing Cox regression models, single-cell RNA sequencing, intercellular communication analysis, and Gene Ontology enrichment. We also conducted mutation profiling and explored potential immunotherapeutic agents. Furthermore, in vitro cellular experiments and in vivo mouse models were performed to validate findings. These methodologies aimed to establish deubiquitination-related gene signatures (DRGS) for predicting ESCC patient outcomes and response to immunotherapy.ResultsBy integrating datasets from TCGA-ESCC and GSE53624, we developed a DRGS model based on 14 deubiquitination-related genes (DUBGs). This signature effectively forecasts ESCC prognosis, drug responsiveness, and immune cell infiltration patterns. It also influences the mutational landscape of patients. Those classified as high-risk exhibited reduced survival rates, increased genetic alterations, and more complex cellular interactions, potentially explaining their poor outcomes. Notably, in vitro and in vivo experiments identified MTOR, a key component of the signature, as a promising therapeutic target for ESCC treatment.ConclusionOur research highlights the significance of 14 DUBGs in ESCC progression. The risk score derived from this gene set enables clinical stratification of patients into distinct prognostic groups. Moreover, MTOR emerges as a potential target for personalized ESCC therapy, offering new avenues for treatment strategies.